Modelling the Present Global Terrestrial Climatic Response Due to a Chicxulub-Type Asteroid Impact - Víctor M. Mendoza; Blanca Mendoza; René Garduño; Marni Pazos (Atmosphere, 2020)
A Chicxulub-like asteroid event occurs, on average, approximately every ~27 to 200 million years. Therefore, such an event could happen presently. Here, we simulate the climatic anomalies it may cause with respect to the current conditions, assuming the same target geology of carbonates and evaporates and a 1 Gt release of sulphate gases. We used a thermodynamic model, including water vapor, cloudiness (by greenhouse and albedo effects), and cryosphere feedback to calculate aerosol cooling. We found that it took nearly 4.5 years for solar radiation to recover its preimpact value—during the first year practically no solar radiation reached the surface. Recovery of the temperature took more than 45 years. The lowest temperatures occurred between 1.5 and 5 years after the impact, being the coldest at −14 °C below the preimpact temperature. July surface temperature anomalies occurred 1.5 years after the impact, becoming one of the largest, compared to preimpact temperatures. Most continents showed temperature anomalies of −45 °C. The least cold places were the polar regions with temperature anomalies between approximately −5 and 0 °C. As for the most remarkable climatic effect, we found that, for ~6 years, the ice extended over almost all the ocean surface and, after ~25 years, it covered nearly half of the surface, remaining so for beyond 45 years. The continental ice remained without reduction beyond 45 years. Sixty years after the impact, the surface oceanic and continental fractions covered by ice were 0.52 and 0.98, respectively. We also modeled the effect of smaller quantities of sulfur released after asteroid impacts, concluding that an instantaneous, large climatic perturbation attributed to a loading range may lead to a semi-permanent shift in the climate system.